2020
DOI: 10.1519/ssc.0000000000000589
|View full text |Cite
|
Sign up to set email alerts
|

Bodyweight BOSU Ball Exercises

Abstract: A growing trend in strength and conditioning is the execution of traditional exercises on instability devices. With the addition of these implements, there is a greater challenge to maintain stability and balance. Implementing a device, such as the BOSU ball, may provide benefits to individuals rehabilitating from an injury, older individuals, and those looking to increase overall health benefits. Thus, this column provides detailed descriptions of the proper technique, advanced progressions, and exercise pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Varus malalignment affects the ability of a person to walk for extended times due to fatigue, and as time passes, the weight of the knee joint is concentrated unevenly, shortening the life span of the joint [9,10]. These symptoms The Asian Journal of Kinesiology | Asian J Kinesiol 2021; 23(3): [20][21][22][23][24][25][26][27][28] . DOI: https://doi.org/10.15758/ajk.2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varus malalignment affects the ability of a person to walk for extended times due to fatigue, and as time passes, the weight of the knee joint is concentrated unevenly, shortening the life span of the joint [9,10]. These symptoms The Asian Journal of Kinesiology | Asian J Kinesiol 2021; 23(3): [20][21][22][23][24][25][26][27][28] . DOI: https://doi.org/10.15758/ajk.2021.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, stretching, which has a positive effect on the joint load of the knee joint, helps rehabilitation of the musculoskeletal system [17][18][19][20][21][22][23] and elastic band exercises with Therabands, and strength exercises on unstable surfaces, i.e. a bosu, can be used to activate stabilizer muscles and help the stability of the joint [24]. As such, most of the preceding studies, especially those using Pilates showed effective improvement in static joint function by improving the knee joint spacing and hip joint motion range, which are varus knee variables due to the improvement of lower extremity muscle strength, but research on how it affects dynamic joint function during walking is insufficient.…”
Section: Introductionmentioning
confidence: 99%